El funcionalismo normativo sistémico. Observaciones sobre su utilidad en la teoría de la pena y la teoría de las funciones del derecho penal - Salazar, Alonso (2016)
This paper focuses on the utility that could have the functionalism normative-systemic on the theory of punishment and functions of criminal law, because is a reality that “at present the scientific and political debate on the death penalty has become, in a debate on the Law Criminal as a whole”.